The Effect Of Supervision And Job Satisfaction On Employee Performance With Employee Commitment As An Intervening Variable In The Tirta Raja Drinking Water Regional Company (Pdam), Ogan Komering Ulu Regency - Yiki Netra; Zunaidah; Marlina Widiyanti; Yuliani; Wita Farla (Jurnal Syntax Transformation, 2024)
- Human resources are an asset in the organization. HR has a very important role in achieving organizational goals and at the same time being the driving force of the organization in achieving and realizing the goals and objectives set. The population of this study was respondents to employees of the Tirta Raja Regional Water Supply Company (PDAM) in Ogan Komering Ulu Regency. The population numbered 180 respondents. The sample is part of the population (part or representative of the population studied). The sample of this study is a portion of the population taken as a data source and can be representative of the entire population. The OKU Regional Drinking Water Company is a Regional Owned Enterprise of Ogan Komering Ulu Regency, which was established in 1979 and fully operational in 1981 by the Department of Public Works, Directorate General of Cipta Karya, Clean Water Sub Project (PAB) South Sumatra under the name of the OKU Drinking Water Management Agency (BPAM). Supervision has a positive and significant effect on the performance of employees at the Regional Water Supply Company (PDAM) Tirta Raja, Ogan Komering Ulu Regency.